Influence of oxygen and culture media on maintenance of whole hamster trachea organ cultures and replication of Sendai virus. - Schiff, L J (1975)
Effects of various oxygen concentrations and culture media on the maintenance of 4-day-old hamster trachea organ cultures and the yield of Sendai virus were studied. The basic media used were Eagle minimal essential medium, medium 199, and CMRL 1066 supplemented with glutamine and antibiotics and buffered with NaHCO3 or N-2-hydroxyethyl-piperazine-N'-2'-ethanesulfonic acid (HEPES). In addition, each medium was evaluated under a gas phase of 5% CO2 and 95% O2, 5% CO2 and 45% O2 and 50% N2, or 5% CO2 and 95% air. Culturing of explants with CMRL 1066 and medium 199 buffered with HEPES in the presence of 5% CO2 and air proved most efficient; ciliary movement and ciliated surface epithelium were maintained for periods up to 27 days. No significant difference in the rate of replication of Sendai virus was seen in the three different media with the two buffer systems in the three different gaseous phases. The addition of 0.2% bovine serum albumin to the media yielded greater quantities of virus, up to 200-fold increase in titer without producing changes in ciliary function. A distinctive pattern of morphological changes was observed in explants of trachea epithelia inoculated with Sendai virus. These results suggest the practical application in the use of whole hamster trachea explants as a diagnostic aid in the isolation of Sendai virus from laboratory rodents.